Android-Based Online ATM Machine Swallowed Bank ATM Card Service Information System - Muh Riyaldi Pratama; Kamaruddin Kamaruddin; John James (Yayasan Cendekiawan Digital Indonesia, 2026)
ATM cards remain a primary means of banking transactions, despite the continued development of digital services. However, operational issues such as ATM cards being swallowed by the machine remain common and are generally handled through inefficient manual procedures that require customers to visit the bank in person. This study aims to develop an Android-based information system for reporting ATM card swappings to improve the efficiency, accessibility, and quality of banking services. The system development method used is the Waterfall model, which includes the stages of needs analysis, system design, implementation, and testing. The resulting system is designed to enable customers to report online, enabling faster handling by customer service without face-to-face interaction. Test results from the black-box testing method indicate that all system features operate according to established specifications and remain stable and functional. The implementation of this system has been proven to increase service response speed, simplify the reporting process, and reduce dependence on conventional procedures. This research contributes to the development of an integrated, real-time, mobile-based complaint service model for banking information systems. In addition, this research also strengthens the role of mobile technology as an enabler in the digital transformation of public services. Thus, the proposed system has the potential to be an effective and adaptive solution in improving service quality and customer satisfaction in the digital era.